2008
DOI: 10.5194/acp-8-1423-2008
|View full text |Cite
|
Sign up to set email alerts
|

Unambiguous identification of esters as oligomers in secondary organic aerosol formed from cyclohexene and cyclohexene/α-pinene ozonolysis

Abstract: Abstract. The build-up of oligomeric compounds during secondary organic aerosol (SOA) formation is subject of atmospheric research since several years. New particle formation and especially the SOA mass yield might be influenced significantly by oligomer formation. However, the chemical nature of observed oligomers and their formation pathways are still unclear. In this paper, the structural characterization of certain dimeric compounds (esters) formed during the ozonolysis of cyclohexene and cyclohexene/α-pin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
104
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 40 publications
9
104
2
Order By: Relevance
“…1). In addition to the MW 358 and 368 esters, minor high-molecular-weight compounds (i.e., MWs 272,300,308,312,314,326,338,344,352,356,376,378 and 400) have also been reported in α-pinene/O 3 SOA (Müller et al, 2008;Yasmeen et al, 2010;Kourtchev et al, 2014;Witkowski and Gierczak, 2014;Zhang et al, 2015) but these products will not be addressed in the present paper. Figure 1.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…1). In addition to the MW 358 and 368 esters, minor high-molecular-weight compounds (i.e., MWs 272,300,308,312,314,326,338,344,352,356,376,378 and 400) have also been reported in α-pinene/O 3 SOA (Müller et al, 2008;Yasmeen et al, 2010;Kourtchev et al, 2014;Witkowski and Gierczak, 2014;Zhang et al, 2015) but these products will not be addressed in the present paper. Figure 1.…”
Section: Introductionmentioning
confidence: 95%
“…Tandem MS on the deprotonated compound (m/z 357) revealed that it has a cis-pinic acid residue (m/z 185) as well as a m/z 171 residue. Later work by Müller et al (2008) focused on the structure of the MW 368 compound. It was shown that this compound is composed of cis-pinic and hydroxypinonic acid parts, which are linked together by an ester bridge.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher-MW products either correspond to non-covalent dimers between monomeric carboxylic acids that are held together by hydrogen bonds (e.g., Hoffmann et al, 1998;Claeys et al, 2009) or to covalent dimers between monomeric carboxylic acids that are connected through covalent bonds, such as, esters (e.g., Hamilton et al, 2006;Szmigielski et al, 2007;Müller et al, 2008) and oligomers formed through gem-diol intermediates (e.g., Gao et al, 2004;Iinuma et al, 2004;Tolocka et al, 2004;Docherty et al, 2005) or aldol condensation reactions (e.g., Tolocka et al, 2004). These heterogeneous processes are consistent 9384 F. Yasmeen et al: Terpenylic acid and related compounds: precursors for dimers in secondary organic aerosol with the observation that sulfuric acid seed aerosol catalyzes the formation of SOA (e.g., Jang et al, 2002Jang et al, , 2003Czoschke et al, 2003;Iinuma et al, 2004).…”
Section: Introductionmentioning
confidence: 99%